2022
DOI: 10.3390/ijerph192013205
|View full text |Cite
|
Sign up to set email alerts
|

When Lights Can Breathe: Investigating the Influences of Breathing Lights on Users’ Emotion

Abstract: Light can significantly influence users’ physiological and behavioural performance. However, how light breathing influences users’ mood regulation remains unknown. To fill this gap, this study conducted a 2-by-2 experiment (N = 20) with light breathing as the between-subject factor and light condition as the within-subject factor. Both physiological indicators and subjective indicators are measured to reflect mood regulation. The data were analysed using a generalised linear mixed model. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…The research article examined whether young children can associate colors with emotions and whether there are any changes in development, and found that white was the most popular color in bedrooms [56]. Wang, J examined the effects of white light breathing with light cool and warm colors on their role as mood regulators for users, and found that over a 5 s cycle, breathing light significantly reduced EDA values and heart rates in people experiencing extreme emotions, thereby reducing tension, while the color temperature had little to no effect on the effectiveness of the breathing light intervention [57]. Seung Hyun Cha, Ph.…”
Section: The Effect Of White Light In Space On Emotionsmentioning
confidence: 99%
“…The research article examined whether young children can associate colors with emotions and whether there are any changes in development, and found that white was the most popular color in bedrooms [56]. Wang, J examined the effects of white light breathing with light cool and warm colors on their role as mood regulators for users, and found that over a 5 s cycle, breathing light significantly reduced EDA values and heart rates in people experiencing extreme emotions, thereby reducing tension, while the color temperature had little to no effect on the effectiveness of the breathing light intervention [57]. Seung Hyun Cha, Ph.…”
Section: The Effect Of White Light In Space On Emotionsmentioning
confidence: 99%